Odpowiedzi

Najlepsza Odpowiedź!
2010-03-05T13:07:20+01:00
A)A=(-5,0),
B=(0,-2),
C=(2,2)
IABI=√[0+5]²+[-2-0]²=√25+4=√29
IBCI=√[2-0]²+[2+2]²=√4+16=√20
IACI=√[2+5]²+[2-0]²=√49+4=√53

[√29]²+[√20]²=[√53]²
29+20=53
49≠53
Ten trójkąt nie jest trójkątem prostokątnym.

b)A=(4,-1)
B= (1,5)
C=(-4,3)
IABI=√[1-4]²+[5+1]²=√9+36=√45
IBCI=√[-4-1]²+[3-5]²=√25+4=√29
IACI=√[-4-4]²+[3+1]²=√64+16=√80

[√45]²+[√29]²=[√80]²
45+29=80
74≠80
Ten trójkąt nie jest trójkątem prostokątnym.

c)A=(-3,-1),
B=(6,-4),
C=(7,-1)
IABI=√[6+3]²+[-4+1]²=√81+9=√90
IBCI=√[7-6]²[-1+4]²=√1+9=√10
IACI=√[7+3]²+[-1+1]²=√100+0=√100=10

[√90]²+[√10]²=10²
90+10=100
100=100
Tak,ten trójkąt jest prostokątny.
1 5 1